Assessing the impact of diet, exercise and the combination of the two as a treatment for OSA: A systematic review and meta‐analysis. Issue 8 (22nd May 2019) - Edwards, Bradley A.; Bristow, Claire; O'Driscoll, Denise M.; Wong, Ai‐Ming; Ghazi, Ladan; Davidson, Zoe E.; Young, Alan; Truby, Helen; Haines, Terry P; Hamilton, Garun S.
ABSTRACT: This study aimed to provide an updated systematic review and meta‐analysis of randomized controlled trials (RCT) investigating the effectiveness of lifestyle interventions on weight loss and the impact on the severity of obstructive sleep apnoea (OSA). A systematic search of five databases between 1980 and May 2018 was used to identify all RCT which employed a lifestyle intervention (i.e. diet‐only, exercise‐only or combination of the two) aiming to reduce the severity of OSA (assessed using the apnoea–hypopnoea index (AHI)). Random‐effects meta‐analyses followed by meta‐regression were conducted. Ten RCT involving 702 participants (Intervention group: n = 354; Control group: n = 348) were assessed in two meta‐analyses. The weighted mean difference in AHI (−8.09 events/h, 95% CI: −11.94 to −4.25) and body mass index (BMI, −2.41 kg/m 2, 95% CI: −4.09 to −0.73) both significantly favoured lifestyle interventions over control arms. Subgroup analyses demonstrated that all interventions were associated with reductions in the AHI, but only the diet‐only interventions were associated with a significant reduction in BMI. No association was found between the reduction in AHI or BMI and the length of the intervention, or with baseline AHI and BMI levels. All lifestyle interventions investigated appear effective for improving OSA severity and should be an essential component of treatment for OSA. Future research should be directed towards identifying subgroups likely to reap greater treatment benefits as well as other therapeutic benefits provided by these interventions. Abstract : See related Editorial